The Effect of Green Spaces on Mitigating the Symptoms of Hyperactivity Disorder and Lack of Attention in Children - Wurood A. Khamees (مجلة النهرين للعلوم الهندسية, 2025)
Children of hyperactivity are like any other children, but they are unable to integrate with society and the environment, because hyperactivity is a developmental disorder that makes the child uncontrollable, difficult to understand, learn and socialize and is placed in the centres of disease control as a serious public health problem. Here, the role of architecture is in its active contribution to improving social interaction and addressing part of the problems of this group of children. This treatment has a significant impact on improving the quality of children's environment in general and children of hyperactivity in particular, thus facilitating interaction and learning with their peers by working to create a healthy environment that meets their needs inside and outside the building. Due to the lack of interest or thorough studies on children with hyper-active, distracted children and the impact of their surrounding environment, whether internal or external, especially within Iraq, despite their considerable and multiple creative potential (physical or mental). Therefore, the aim of the research was to determine the extent of the effect of green on the elite or hyperactivity symptoms of children suffering from hyperactivity syndrome, and to contribute to their positive, sensory and collective appearance.